Ultrasound-Assisted Modification of Insoluble Dietary Fiber from Chia (Salvia hispanica L.) Seeds - Zohaib Hassan; Muhammad Imran; Muhammad Haseeb Ahmad; Muhammad Kamran Khan (Journal of Food Quality)
Modification of insoluble dietary fiber (IDF) to soluble dietary fiber (SDF) improves not only the various health benefits but also the functional properties for improved product development. This research aimed to examine the effects of sonication treatment on the functional and physicochemical properties with possible structural changes in chia seeds dietary fiber. Central composite design was applied to optimize the sonication treatment process (amplitude 55%, time 20 min, and temperature 40°C) based on the oil holding capacity (OHC) and water holding capacity (WHC) as responses. Under these optimum conditions, ultrasound-treated IDF exhibited better functional and physicochemical properties such as OHC, WHC, glucose adsorption capacity (GAC), and water retention capacity (WRC) than untreated IDF. Fourier-transform infrared spectroscopy further confirmed the structural changes in treated and untreated IDF to explain the changes in the studied parameters.